The first three steps for solving the quadratic equation by completing the square are shown. Fill in the missing number in the last step.

9x2 +54x = 7

9(x2 + 6x) = 7

9(x2 + 6x + 9) = 7 +.?

Respuesta :

Completing the square is done as follows:

1. Write the equation in a way that the constants are in the right side while the terms with x are on the left. 
9x2 +54x = 7

2. Make sure that the coefficient of the x^2 term is 1.
9(x2 + 6x) = 7

3. Adding a term to both sides that will complete the square in the left side. This is done by dividing the coefficient of the x term by 2 and squaring it. Note: The same amount should be added to the right side to balance the equation.
9(x2 + 6x + 9) = 7 + 81

9(x+3)^2 = 88

Answer:

? = 81

Step-by-step explanation: